The Epigraphic Digital Lab: Teaching Epigraphy in the Twenty-First Century c.e - Parker, Heather Dana Davis (Near Eastern archaeology, 2016)
The dictum “nothing ever stays the same” is certainly true of academics. Fields of knowledge are always in transition, and the field of Northwest Semitic epigraphy is no exception to this. Data continue to accumulate, methods of data analysis are constantly being refined, analyses of data are continually nuancing previous understandings and conclusions, and ways of presenting such conclusions often change. This paper focuses on the technological innovations that are impacting the study of inscriptions. A primary focus will be the use of digital technology in drawing ancient texts and palaeographic script charts and how to teach this technology in an epigraphic digital lab. Emphasis will be placed on the linear alphabetic Northwest Semitic corpus; however, the technologies, techniques, and methodologies discussed can be applied to other epigraphic fields.